Effect of Taichi Chuan on health-related physical fitness in adults: A systematic review with meta-analysis - Fengmeng Qi; Kim Geok Soh; Nasnoor Juzaily Mohd Nasiruddin; Ong Swee Leong; Sun He; Huange Liu (Elsevier, 2023)
Purpose: Taichi Chuan was previously shown to benefit physical health, but the results were inconsistent. The main reason is that the mechanism is not clear and may be interpreted differently. In this systematic review, we analyzed the data obtained from various randomized controlled trials to identify the effectiveness of Taichi Chuan and the mechanism by which it improves the physical health of adults. Methods: We systematically searched various databases, including PubMed, Web of Science, Scopus, Embase, EBSCO Host, Science Direct, CNKI, Wan-Fang, and VPCS, and obtained 1448 articles for review. The articles were selected following the PICO eligibility criteria. We performed a systematic review and meta-analysis to interpret the results of the different studies. Results: We included 16 studies in the systematic review. Six of them were of very high quality, ten were of acceptable quality. Overall, the results showed that Taichi Chuan is beneficial to physical fitness, but not all indices supported this statement. Specifically, the effects were significant on Balance (ES = − 0.33; P = 0.02), BMI (ES = − 0.83; P < 0.00001), body fat (ES = − 0.45; P < 0.00001), and vital capacity (ES = 23.39; P = 0.01). However, there were no significant effects on systolic blood pressure (ES = 0.07; P = 0.94) and diastolic blood pressure (ES = 0.03; P = 0.97). Conclusion: We found sufficient high-quality evidence to suggest that Taichi Chuan affects balance, BMI, body fat, vital capacity, and flexibility (sit-reach) in adults. The mechanism can be explained by low posture (balance) and moderate intensity of Taichi Chuan. However, no study has explained how to maintain concentration while keeping a dynamic low posture, which made it difficult to validate the finding that Taichi Chuan can reduce sympathetic tension under stress. In this study, we assumed that relaxation methods, which work on the central nervous system that links the body and the mind, might be the key explanation. However, further studies based on scientific, replicable methods need to be performed to confirm our findings.